Rewarding Aggression in Ovariectomized Female Mice - Blasetti, Brittany. (Tufts University. Tisch Library., 2025)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Psychology.; Advisors: Marcus Weera, and Elizabeth Race.; Committee: Marcus Weera, Elizabeth Race, and Jamie Maguire.; Keywords: Experimental psychology, Neurosciences, and Behavioral psychology.